Empowering Local Fish Farmers Through Hormonal-Based Induced Spawning of Climbing Perch (Anabas testudineus) for Sustainable Aquaculture Production - Mirna Fitrani; Revita Syefti Palmi; Aliya Hafidzah; Edward Saleh; Ngudiantoro Ngudiantoro; M. Nursan (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: Climbing perch (Anabas testudineus) is a primary commodity in Ogan Ilir Regency, South Sumatra, with high market demand. However, wild populations are declining due to overfishing, and farmers face a chronic shortage of high-quality fry due to seasonal spawning limitations. Purpose: This community service program aims to empower local fish farmers through hormonal-based induced spawning technology and participatory training to increase fry production capacity and improve farmers' competence. Methods: The program used a Participatory Action Research (PAR) approach with three phases: planning (FGDs), implementation (hormone injection, spawning, larval rearing), and evaluation (pre/post-test). Participants were 15 farmers from Pokdakan Balai Makmur. Spawning used 0.25 mL/kg Ovaprim and 0.90 mL/kg hCG. Parameters measured included fecundity (F), fertilization rate (FR), hatching rate (HR), survival rate (SR), and farmer competence. Results: Fecundity reached 6,326 eggs per female. FR was 98.6% (SD ±0.81), HR was 96.3% (SD ±1.20), and SR was 99.1% (SD ±0.51). Water quality remained optimal (pH 6.5–8.8, temperature 25.8–29.4°C, DO 5.0–5.5 mg/L). Farmer competence improved from 25.8% (SD ±8.2) to 60.5% (SD ±7.4), a significant increase of 34.7 percentage points (paired t-test, p < 0.001). A community-managed